Antifungal Resistance Patterns in Dermatophytic Infections: A Regional Analysis - Siddiqui, Md Mujibur Rahman; Babar, Zahir Uddin Mohammad; Shaheen, Md Nazrul Islam (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Dermatophytic infections, caused by Trichophyton, Microsporum, and Epidermophyton species, are common skin problem. Recently, antifungal resistance has arisen as a serious barrier in controlling these diseases, particularly in areas where antifungal drugs are widely used. Objective: The objective of this study was to evaluate the antifungal resistance patterns of dermatophytes isolated from patients with dermatophytosis and assess the resistance patterns of dermatophytes to routinely used antifungal drugs (terbinafine, itraconazole, and fluconazole) in dermatophytosis patients. Methods: This cross sectional observational study conducted at Department of Dermatology, Estern Medical College & Hospital from July 2023 to June 2024. A total 120 patients diagnosed with dermatophytosis who received antifungal treatment for their dermatophyte infections are included in this study. Data on patient demographics, treatment history, and antifungal resistance patterns were collected and analyzed. Results: Among 120 patients, Trichophyton rubrum was the most common dermatophyte species (69.44%). T. rubrum had the strongest resistance to fluconazole (32%), followed by itraconazole (20%) and terbinafine (16%). Trichophyton mentagrophytes showed comparable resistance patterns, with fluconazole resistance reaching 36%. Resistance was reduced in Microsporum canis and Epidermophyton floccosum. A significant association was found between prior antifungal treatment and increased resistance. Conclusion: This study reveals a significant development in antifungal resistance among dermatophytes, notably to fluconazole, emphasising the importance of regular susceptibility testing and judicious antifungal use. J Com Med Col Teachers’ Asso Jan 2025; 29(1):65-69